Methylthiolation for Electron‐Rich Heteroarenes with DMSO‐TsCl - Zhang, Lei‐Yang; Wu, Yue‐Hua; Wang, Nai‐Xing; Gao, Xue‐Wang; Yan, Zhan; Xu, Bao‐Cai; Liu, Ning; Wang, Bo‐Zhou; Xing, Yalan (European journal of organic chemistry, 2021)
DMSO‐TsCl has been developed for direct methylthiolation of various electron‐rich heteroarenes (more than 40 examples) with high regioselectivity in moderate to excellent yields (up to 96 %). Especially, pyrroles, furans, and thiophenes can be efficiently mono‐methylthiolated. This practical method features scalable, metal‐free, mild conditions and is compatible with air and moisture. Several applications of methylthiolated products were demonstrated for the first time. Based on controlled experimental results, a plausible mechanism was proposed with two key intermediates involved in the mechanism being detected by HRMS. DMSO‐TsCl is developed for methylthiolation of various heteroarenes including pyrroles, furans, thiophenes and indoles under facile conditions. This protocol features scalable, general applicability of substrates and moderate to excellent yields. An acceptable mechanism is proposed, two of the key intermediates of proposed mechanism are detected by HRMS. Further applications of this method were also conducted.